Intel's official guide to 386 computing. - Edelhart, Michael (Osborne McGraw-Hill, 1991)
"Now that you have your 386™ microprocessor-based PC, you'll want to learn how to take full advantage of its features to get the most from your investment. Intel's Official Guide to 386™ Computing is the book to choose for • Enhancing your 386 computer for maximum power. • Turning a 286 PC into a 386 PC. • Getting the most from Microsoft® Windows 3.0 and UNIX® on your 386 PC. • Making every application program run better and easier with the 386 chip. Intel's Official Guide to 386™ Computing, written by PC Computing's Editor -in-Chief Michael Edelhart, with chapters contributed by experts in the field and reviewed by Intel Corporation, has the inside information you've been looking for. Intel's Official Guide to 386™ Computing • Covers every aspect of what your 386 computer can do. • Discusses 386 microprocessor hardware, system software, and applications software. •Provides a guide to programming tools for 386 PC systems. •Spans the 386 PC family from the 386™ SX™ CPU notebook to the 33MHz 386™ DX CPU network server. Intel's Official Guide to 386™ Computing įs the best book to help you become more productive with your 386 computer." (Copied from the paste).